THE CHURCH-MEDIA RELATIONSHIP: HOW DOES THE PROFANE MEDIA TREAT THE SACRED MESSAGE? - RONČÁKOVÁ, TERÉZIA (Espaço e Cultura, 2018)
The coexistence of mass media and the Church draws the attention of scholars due to the existence of a sort of ‘subliminal’ conflict. This conflict has been widely examined and has led to many interesting and inspiring results. This paper attempts to address the causes of the current state drawing on the generally known facts and extensive experience of a common media consumer, and provides several valuable insights based on author´s previous research. Before exploring the actual causes, the author clarifies the following two starting points of her examination: the position of journalists (what annoys them about the Church and, conversely, what they welcome in her approach) and the position of the Church (what annoys her about journalists and conversely, what she welcomes in their approach). After clarifying some causes, she turns her attention to the consequences; adding, finally, a short provocative reflection.